Effect of Temperature Variations on Strain Response of Polymer Bragg Grating Optical Fibers - Hisham, Hisham K. (Iraqi Journal for Electrical and Electronic Engineering, 2017)
This paper presents a numerical analysis for the effect of temperature variations on the strain response of polymer optical fiber (POF) Bragg gratings. Results show that the dependence of the Bragg wavelength (λ B ) upon strain and temperature variations for the POF Bragg gratings is lies within the range of 0.462 – 0.470 fm με -1 °C -1 compare with 0.14 – 0.15 fm με -1 °C -1 for the SOFs Bragg gratings. Also, results show that the strain response for the POF Bragg gratings changed on average by 1.034 ± 0.02fm με - important for strain sensor applications especially in the environments where the temperature change.